Analisis Kelayakan Usahatani Padi Varietas Meraoke, Dyah Suci dan Ciliwung dengan Menggunakan Revenue Cost Ratio (R/C Rasio) - Ovilia Nivo Ringan; Untari Untari; Ineke Nursih Widyantari (AGRICOLA, 2018)
This research was aims to analyze the feasibility of paddy varieties Meraoke, Dyah Suci andCiliwung in paddy fields by using the Revenue Cost Ratio (R/C ratio) in the district of Merauke. Theresearch was conducted in Marga Mulya village Semangga District starts from September 2012 toJanuary 2013. The type of data in this research is the primary and secondary data. Data analysisperformed in this study is an analysis of the feasibility of farming by using the Revenue Cost Ratio(R/C ratio). Results of the analysis of the feasibility of using a proportion of farm receipts and cost(R/C ratio) with more than 1,5 criteria. Meraoke rice varieties with a variety of inorganic treatmentwith treatment eligibility level or value of the R/C ratio of 1.55 which is lower if compared with therice varieties of organic semi Meraoke treatment value of R/C ratio of 2.06 and the Dyah Sucitreatment of rice varieties inorganic value of R/C ratio obtained at 2.70 and varieties of organic semicommission of the Dyah Suci R/C ratio of 2.37 obtained rice varieties and inorganic treatmentCiliwung R/C ratio of 3.45 and obtained treatment Ciliwung organic semi R/C ratio obtained by 2.14.